Examining the Role of FOMO in TikTok Storytelling on Purchase Decisions of One Piece Comics - Alberta Adinata; Sudarmiatin; Heri Pratikto (International Journal of Economics and Management Sciences, 2026)
Digital transformation has reconstructed the marketing landscape, positioning TikTok as a narrative and affective space that significantly shapes consumption decisions. This study investigates the interaction between Storytelling Marketing (STM), Electronic Word of Mouth (e-WOM), and Fear of Missing Out (FOMO) in influencing and mediating One Piece comic purchase intention. Using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach involving 385 respondents, the findings reveal that STM and e-WOM not only exert a direct effect on purchasing decisions but also generate psychological resonance manifested as FOMO, which further strengthens consumers’ impulsive and consumptive tendencies. In this context, TikTok functions not merely as a digital platform, but as an affective field where narratives, emotions, and social pressures intertwine, blurring the boundaries between storytelling and economic decision-making. The results highlight that content strategies on social media operate as mechanisms of meaning construction that activate symbolic ownership through collective emotional urgency. Thus, consumption behavior is shaped not only by rational evaluation but also by socially constructed emotional experiences embedded within digital interactions on TikTok.